2005
DOI: 10.1105/tpc.105.036814
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASES1 and 2 Control Male Sporogenesis

Abstract: The Arabidopsis thaliana SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK) family of plasma membrane receptors consists of five closely related members. The SERK1 and SERK2 genes show a complex expression pattern throughout development. Both are expressed in anther primordia up to the second parietal division. After this point, expression ceases in the sporocytes and is continued in the tapetum and middle layer precursors. Single knockout mutants of SERK1 and SERK2 show no obvious phenotypes. Double mutants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
286
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(305 citation statements)
references
References 58 publications
12
286
1
6
Order By: Relevance
“…affect (in a nonmutually exclusive manner) phosphorylation events within the PRR-BAK1 complex, association and/or dissociation with downstream components, and phosphorylation events with direct substrates. It is becoming increasingly clear that, in addition to their role in BR responses, BAK1 and other SERKs in Arabidopsis and other plant species are master regulators of plant innate immunity (Heese et al, 2007;Shan et al, 2008;Fradin et al, 2009Fradin et al, , 2011Santos et al, 2009;Bar et al, 2010;Krol et al, 2010;Chaparro-Garcia et al, 2011;Mantelin et al, 2011;Roux et al, 2011;Yang et al, 2011) as well as of cell death control Kemmerling et al, 2007;Gao et al, 2009;Wang et al, 2011), pollen development (Albrecht et al, 2005;Colcombet et al, 2005), and organ abscission (Lewis et al, 2010). One must not assume that the model based on analyses between BRI1 and BAK1 is universal, and, in light of our results, it is essential that researchers analyze in detail and quantify the impact of modifying the SERK proteins in transgenic approaches when studying SERKdependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…affect (in a nonmutually exclusive manner) phosphorylation events within the PRR-BAK1 complex, association and/or dissociation with downstream components, and phosphorylation events with direct substrates. It is becoming increasingly clear that, in addition to their role in BR responses, BAK1 and other SERKs in Arabidopsis and other plant species are master regulators of plant innate immunity (Heese et al, 2007;Shan et al, 2008;Fradin et al, 2009Fradin et al, , 2011Santos et al, 2009;Bar et al, 2010;Krol et al, 2010;Chaparro-Garcia et al, 2011;Mantelin et al, 2011;Roux et al, 2011;Yang et al, 2011) as well as of cell death control Kemmerling et al, 2007;Gao et al, 2009;Wang et al, 2011), pollen development (Albrecht et al, 2005;Colcombet et al, 2005), and organ abscission (Lewis et al, 2010). One must not assume that the model based on analyses between BRI1 and BAK1 is universal, and, in light of our results, it is essential that researchers analyze in detail and quantify the impact of modifying the SERK proteins in transgenic approaches when studying SERKdependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that single knockout mutant of either SERK1 or SERK2 shows no obvious phenotypes, but double mutants are male sterile due to defect in tapetum differentiation, a phenotype similar to that caused by mutation of another LRR-RLK, ems1 [34]. These results suggest that SERK1 and SERK2 are functionally redundant in reproductive development [35]. It is unclear whether the function of SERK1 and SERK2 in reproductive development is related to BR signaling.…”
Section: Tissue Specific Functions Of the Homologs Of Bri1 And Bak1mentioning
confidence: 99%
“…This approach has been successfully used to detect interactions between membrane-bound LRR-RLKs, such as the SERK family members (SERK1, SERK2, BAK1, and BAK1-LIKE1), and BAK1-INTERACTING RECEPTOR-LIKE KINASE1 (Russinova et al, 2004;Albrecht et al, 2005;Karlova et al, 2006;Gao et al, 2009). To facilitate this analysis, constructs to express full-length versions of CST, HAE, and EVR with C-terminal translational fusions to either the N-terminal half of YFP (YFPn) or the C-terminal half of YFP (YFPc) were generated.…”
Section: Cst Interacts With the Hae And Evr Rlks At The Plasma Membranementioning
confidence: 99%